The Impact of Information Quality on the Strategic Choice Process in Business Organizations Case Study of the Tebessa Phosphate Mines Company - chafa, hamad (Journal of Excellence for Economics and Management Research, 2025)
The study aims to identify the impact of information quality on the strategic choice process by utilizing the dimensions of information quality (information accuracy, comprehensiveness, clarity, flexibility, and timeliness of information), considering that information and its quality are among the most important inputs to the strategic choice process, especially when selecting the appropriate strategic alternative. A questionnaire was used as the primary tool to collect the necessary data. The study included testing a main hypothesis and sub-hypotheses to determine the relationship between the independent and dependent variables using the statistical software program (SPSS). The study reached a set of conclusions, the most prominent of which was the impact of information quality at each stage of the strategic choice process. It also found a correlation between information quality and the strategic choice process in the institution under study. In light of the findings, the study presented a set of recommendations, the most important of which was the implementation of the strategic alternative chosen by the institution under study.